Repurposing glycated hemoglobin as a possible marker of myocardial ageing in asymptomatic older adults. (25th November 2020) - Koh, A; Gao, G.F; Chow, V.C; Chew, H.C; Ewe, E.S.H; Teo, L.T; Keng, B.M.H; Tan, R.S; Leng, L.S; Zhao, X.D; Zhong, L; Tan, H.C; et al.
Abstract: Background: The adverse consequences of diabetes mellitus on cardiovascular health is well-established. However, few studies have studied the impact of diabetes on ageing. In our previous investigations, we identified distinct patterns of myocardial ageing among older adults otherwise asymptomatic for clinical cardiovascular disease. In this analysis, we hypothesize that glycated hemoglobin (HbA1c) may be differentially associated with these distinct signatures of myocardial ageing, thereby providing greater precision towards future preventative trials. Methods: We performed extensive cardiovascular examinations on a cohort of asymptomatic aged community adults. Transthoracic echocardiography measured left ventricular structure and function. LV filling pressure was measured as the ratio between early mitral inflow velocity and mitral annular early diastolic velocity. Longitudinal left atrial (LA) strain comprising reservoir strain (ɛs), conduit strain (ɛe) and booster strain (ɛa) and their corresponding peak strain rates (SRs, SRe, SRa) were measured using cardiac magnetic resonance (CMR) feature tracking technique. Blood sampling for biomarkers were performed simultaneously with cardiovascular examinations. Results: Among n=515 community adults in sinus rhythm and without cardiovascular disease [mean age 73±4 years, 255 (50%) females], 116 (23%) had diabetes. Age (73 vs 73 years) and heart rate (72 vs 75 beats per minute) were similar between diabetic and non-diabetic older adults. Diabetic older adults are mostly male (59% vs 48%, p=0.046), had larger body mass indices (24 vs 23 kg/m 2, p=0.027), and greater burdens of hypertension (81% vs 41%, p<0.0001) and dyslipidemia (79% vs 43%, p<0.0001), compared to non-diabetic older adults. Diabetics had worse LV myocardial relaxation [(ratio of peak velocity flow in early diastole E (m/s) to peak velocity flow in late diastole by atrial contraction A (m/s), 0.8±0.2 vs 0.9±0.3, p=0.031), worse LV filling pressures (10.9±3.1 vs 10.1±3.3, p=0.022), reductions in LA global strain (−33±17 vs −28±9.7, p=0.016), LA conduit strain ɛe (12±4.3 vs 14±4.1, p=0.045), increases in SRe (−1.2±0.4 vs −1.3±0.5, p=0.042) and reductions in SRe: SRa ratio (0.5±0.2 vs 0.7±0.3, p=0.0059) compared to non-diabetics. Based on multivariate analysis, HbA1c was independently associated with LV myocardial relaxation (β=−0.08 (−0.1, −0.03), p=0.002), LA conduit strain (β=−0.9, (−1.6, −0.1), p=0.025), LA conduit strain rate (β=0.1, (0.04, 0.2), p=0.005), strongly associated with LA global strain (β=3.0, (0.9, 5.1), p=0.006), but not associated with LV filling pressure (β=0.5 (−0.04, 1.0), p=NS). Conclusion: Our detailed examinations revealed distinct associations between glycated hemoglobin and myocardial functions that additionally varied in magnitude. As a contemporary biomarker, glycated hemoglobin may be useful for stratifying risks associated with myocardial ageing, particularly in ageing-related left atrial myopathies. Funding Acknowledgement: Type of funding source: Public Institution(s). Main funding source(s): National Medical Research Council of Singapore; Singhealth Foundation